Plasmin Generation Plays different Roles in the Formation and Removal of Arterial and Venous Thrombus in Mice - Matsuno, Hiroyuki; Kozawa, Osamu; Okada, Kiyotaka; Ueshima, Shigeru; Matsuo, Osamu; Uematsu, Toshihiko (Thrombosis and Haemostasis, 2002)
The role of plasminogen (Plg) and α2-antiplasmin (α2-AP) in vascular thrombolysis in vivo was investigated in mice deficient in plasminogen (Plg−/−) or α2-AP (α2-AP−/−) or their wild type (PAI-1+/+, α2AP+/+). A thrombus was induced in the murine carotid artery or the internal jugular vein by endothelial injury. Blood flow was continuously monitored for 90 min and for 6 h 30 min after the initiation of endothelial injury. The times to occlusion by the developing thrombus in the carotid artery and the jugular vein of wild type mice were 12 ± 1.8 and 7.2 ± 1.9 min, respectively. The arterial thrombus formation in α2AP−/− mice was indistinguishable from the one in wild type mice, whereas the time to occlusion in Plg−/− was significantly shortened to 5.9 ± 1.7 min. Vascular patency after spontaneous reperfusion was markedly improved in α2-AP−/− mice. On the contrary, arterial patency in Plg−/− mice was aggravated. In venous thrombus formation, the time to occlusion in α2-AP−/− mice was significantly prolonged (27.1 ± 5.2 min), whereas in Plg−/− it was slightly shortened to 6.5 ± 2.5 min. Vascular patency after spontaneous reperfusion was also improved in α2-AP−/− mice, but not in Plg−/− mice. Histological observations using SEM indicated that fibrin nets were firmly fixed on the injured area in Plg−/− mice, but not in α2-AP−/− mice. The tail bleeding time was not different in any type of mice. However, re-bleeding time using a template bleeding device was significantly prolonged in α2-AP−/− as compared with that of wild type mice. In conclusion, lack of plasminogen markedly reduces the antithrombotic activities in vivo, whereas α2-AP plays a more important role in the formation and removal of venous thrombus in mice. Consequently, the inhibition of α2-AP could be a useful tool for the therapy of venous thrombosis and the prevention of re-thrombus formation.
Keywords: α2-AP; gene-inactived mice; plasminogen; reperfusion; thrombus